2020
DOI: 10.1177/0271678x20968032
|View full text |Cite
|
Sign up to set email alerts
|

Blood lipid markers are associated with hippocampal viscoelastic properties and memory in humans

Abstract: Age-related memory loss shares similar risk factors as cardiometabolic diseases including elevated serum triglycerides (TGs) and low-density lipoprotein cholesterol (LDL-C) and reduced high-density lipoprotein cholesterol (HDL-C). The mechanisms linking these aberrant blood lipids to memory loss are not completely understood but may be partially mediated by reduced integrity of the hippocampus (HC), the primary brain structure for encoding and recalling memories. In this study, we tested the hypothesis that bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 93 publications
1
4
0
Order By: Relevance
“…Eighty-eight participants were included from three different studies (age range: 23-81 years, M/F: 36/51); all participants completed identical one-hour MRI scanning protocols on a 3T Siemens Prisma MRI scanner. Subsets of these data have been previously reported (Delgorio et al, 2021;Sanjana et al, 2021). We confirmed MRE data quality for each participant in our sample, as quantified by octahedral shear strain signal-to-noise ratio (OSS-SNR), and all 88 participants had OSS-SNR values greater than the threshold of 3.0 necessary for stable property estimation (McGarry et al, 2011;Hannum et al, 2021).…”
Section: Methodssupporting
confidence: 79%
“…Eighty-eight participants were included from three different studies (age range: 23-81 years, M/F: 36/51); all participants completed identical one-hour MRI scanning protocols on a 3T Siemens Prisma MRI scanner. Subsets of these data have been previously reported (Delgorio et al, 2021;Sanjana et al, 2021). We confirmed MRE data quality for each participant in our sample, as quantified by octahedral shear strain signal-to-noise ratio (OSS-SNR), and all 88 participants had OSS-SNR values greater than the threshold of 3.0 necessary for stable property estimation (McGarry et al, 2011;Hannum et al, 2021).…”
Section: Methodssupporting
confidence: 79%
“…The association between lipid profile elevation and brain function dysfunction has not yet been elucidated, but recently, it has been shown that an increase in lipid profile can partially reduce the integrity of the hippocampus, the primary brain structure for encoding and recalling memories. Hippocampus viscoelasticity is negatively associated with serum TG levels and the TG/HDL-C ratio [ 43 ]. In this regard, the results of this study showed that diabetes decreases the general locomotor activity and passive avoidance, and cognitive memory, but anxiolytic activity, despite an insignificant increase, was not affected by diabetes induction.…”
Section: Discussionmentioning
confidence: 99%
“…Other than the obesity parameters, dyslipidemia also showed an independent correlation with deteriorated cognitive function. Findings from general population suggest that even modest, preclinical changes in lipid metabolism may be sufficient to evoke changes to hippocampus structure and function, which is responsible for encoding and recalling memories [ 33 ]. And simvastatin and lovastatin are drugs that can potentially be used for the treatment of cognitive deficits [ 34 ].…”
Section: Discussionmentioning
confidence: 99%